2015
DOI: 10.5770/cgj.18.184
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clerkship Observerships to Increase Early Exposure to Geriatric Medicine

Abstract: Background and PurposeTo foster interest in geriatric care, the Queen’s Geriatrics Interest Group (QGIG) collaborated with the Division of Geriatric Medicine to arrange a Geriatrics Pre-Clerkship Observership Program.MethodsForty-two pre-clerkship medical students participated in the program between October 2013 and May 2014. Participants were paired with a resident and/or attending physician for a four-hour weekend observership on an inpatient geriatric rehabilitation unit. The program was assessed using: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In our study, most students reported increased or confirmed interest in a surgical career after their observership, which is consistent with previous studies. 13 , 14 However, in line with a study assessing a similar student-led initiative in geriatric medicine, 15 we did not observe a significant change in the students’ choices of surgical specialties after the observership. This outcome was expected given the high proportion of students reporting an interest in surgery before their observerships, which resulted in a plateau effect.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, most students reported increased or confirmed interest in a surgical career after their observership, which is consistent with previous studies. 13 , 14 However, in line with a study assessing a similar student-led initiative in geriatric medicine, 15 we did not observe a significant change in the students’ choices of surgical specialties after the observership. This outcome was expected given the high proportion of students reporting an interest in surgery before their observerships, which resulted in a plateau effect.…”
Section: Discussionsupporting
confidence: 84%
“…This outcome was expected given the high proportion of students reporting an interest in surgery before their observerships, which resulted in a plateau effect. Although it has been suggested that a significant change could be detected in a larger study population, 15 we believe that the selection of participants has a greater influence on results. As samples are often composed of participants presenting an interest in the specialty, changes would be more difficult to identify, even in a larger sample.…”
Section: Discussionmentioning
confidence: 82%
“…Our findings build on previous work that has demonstrated improvements in knowledge, clinical skills, and empathy among undergraduate and graduate medical trainees. [6][7][8][9][10][11][12][13][14][15] In particular, studies designed to evaluate the perceptions of medical and pharmacy students have demonstrated a positive influence of interprofessional activities with respect to geriatric medicine. Shrader et al 23 described an in-home interview and medication history activity with local volunteers, in which students were assessed on attitudes toward other health professionals before and after the experience, demonstrating gains in the importance in collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to increase early student exposure to geriatric medicine using extracurricular time, Queen’s University introduced a structured pre-clerkship observership program that resulted in high student participation, good care of the elderly role-modelling, and stimulated student interest in a career in geriatric medicine. 39 The application of innovative and system-wide programs like the above demonstrate that effective leadership can translate to more inclusive teaching and promote a non-ageist culture.…”
Section: Introductionmentioning
confidence: 99%